Retrospective Analysis of High-Dose Intrathecal Morphine for Analgesia after Pelvic Surgery - Annette Rebel; Paul Sloan; Michael Andrykowski (Pain Research and Management)
BACKGROUND: The effectiveness of intrathecal opioids (ITOs) for postoperative analgesia has been limited by reduced opioid dosing because of opioid-related side effects, most importantly respiratory depression. To overcome these limitations, high-dose intrathecal morphine was combined with a continuous intravenous (IV) postoperative naloxone infusion. The aim of the present chart analysis was to investigate the safety and efficacy of high-dose ITOs combined with IV naloxone compared with IV opioid analgesia alone.